Simulating the impacts of distal volcanic products upon peatlands in northern Britain:An experimental study on the Moss of Achnacree, Scotland - Payne, Richard; Blackford, Jeff (Journal of Archaeological Science, 2005)
The potential impact of prehistoric volcanism on distal areas has been the subject of some discussion in both ecology and archaeology. An experimental approach is used here to examine the potential effects of distant volcanism on a peatland environment. Simulations of different tephra and acidity loading, designed to approximately replicate the prehistoric Hekla-4 ashfall, were monitored over 2 years. Impacts on the peatland ecosystem were assessed by qualitative observations of plant health and abundance, semi-quantitative observations of flowering, measurements of peat pH, humification and testate amoebae community composition. Plots with higher acid loading showed immediate and lasting impacts on plants, although other treated plots were less affected. Changes in testate amoebae and peat humification were inconsistent both within and between plots. The experiment demonstrates the potentially severe effects of high acid loading on peatland plants, although some responses remain unclear.